Kecerdasan Kultural (CI): Membangun Pendidikan Bermutu Total - Hubertus Muda (Jurnal Alternatif Wacana Ilmiah Interkultural, 2013)
The article introduces the basic concept of “Cultural Intelligence" (CQ),a theoretical framework for evaluating effectiveness in intercultural interaction. Each of the four major components is decribed: Knowledge CQ (understanding cultural differences); Interpretive CQ(ability to interpret cues); Perseverance CQ(persevering though intercultural conflict) and behavioural CQ (acting appropriately).To help readers understand the practical implications of these categories, the article develops a recurring case example in Education. By describing some of their inaccurate assumptions and inappropriateness behaviours, a clear picture emerges ofhow CQ operates practically. Total Quality Education(TQE)based on Total Quality Management (TQM) very much count on how is Cultural Intelligence (Cl) put in practice regularly.